(untitled) (Nigerian Journal of Physiological Sciences, 2020)
Summary: One of the major occupation-related health challenges encountered by wood workers is respiratory disorder, which usually results from breathing in noxious or toxic chemicals such as wood dust. The aim of this study is to evaluate the respiratory functions and symptoms among wood workers exposed to varying degrees of wood dust in Kano, Nigeria. This descriptive cross-sectional study was carried out among 370 randomly selected wood workers in Kano wood market. Lung function test was performed, while semi-structured interviewer administered questionnaire was used to rate respiratory symptoms. The study demonstrated that there was low percentage predicted force expiratory volume at one minute (PPFEV1) and percentage predicted ratio of FEV1 and FVC, whereas, the percentage predicted forced vital capacity (PPFVC) of the respondents across all age groups remained unchanged. Similarly, a negative correlation was observed between degree of exposure to the hazards and lung function of the workers (r = -0.655, P-Value = 0.0001). A statistically significant association existed between exposure to wood dust and respiratory symptoms, thereby contributing to the observed manifestation of respiratory symptoms such as chronic cough, corrhiza, breathlessness and wheezing among 61% of wood dust exposed workers. Keywords: Wood workers, Wood dust, Occupational hazard, Lung function, Respiratory symptoms